Zastosowanie Modelu «Śnieżnego Pługa» do Rurki Uderzeniowej ze Współosiowymi Elektrodami - Byszewski, W.W.; Kopsytyński, J.; Mucha, Z.; Pietrzyk, Z.A. (Engineering Transactions, 1965)
The object of the considerations is the process of acceleration of plasma in a shock tube with concentric electrodes which is described theoretically by means of the «snow plough models, using this model a computation is performed assuming constant inductivity of the circuit. The error resulting from this assumption is estimated. A comparison of the theoretical and experimental results shows, in principle, a qualitative agreement between corresponding relations and quantitative differences which amount to some 100 percent.